2020
DOI: 10.3390/genes11070814
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Receptor D299G/T399I Haplotype Polymorphism Is Associated with Insulin Resistance in Obese Female Subjects

Abstract: Background: Activation of Toll-like-receptor 4 (TLR4) causes chronic inflammation that can result in obesity and metabolic syndrome (MeS). Aim: This study aimed to investigate the role of TLR4 polymorphisms of TLR4D299G/T399I, and its impact on protein expression of TLR4 in obese female subjects. Methodology: A prospective cross-sectional association study was performed on Arab female subjects from Qatar University. The subjects were categorized according to BMI classifications into two groups: “obese; n = 69”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(58 reference statements)
1
5
0
Order By: Relevance
“… 22 Several studies demonstrated that hsCRP seems to be the single biomarker of inflammation observed to consistently decreased after bariatric surgery. 23 , 24 Furthermore, the present study demonstrated a decrease of pro-inflammatory cytokines of TNF-alpha and IL-6, which is coherent with previous studies, 15 , 17 while other studies demonstrated no changes. 18 , 19 The inconsistent results of inflammatory cytokines profile between different studies could be due to the degree of insulin resistance at baseline, inflammatory markers’ expression, sample size, study design, technical assays, the timing of assessment of postoperative outcomes, and inherited factors of the study population, which could impact the heterogeneity among the studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 22 Several studies demonstrated that hsCRP seems to be the single biomarker of inflammation observed to consistently decreased after bariatric surgery. 23 , 24 Furthermore, the present study demonstrated a decrease of pro-inflammatory cytokines of TNF-alpha and IL-6, which is coherent with previous studies, 15 , 17 while other studies demonstrated no changes. 18 , 19 The inconsistent results of inflammatory cytokines profile between different studies could be due to the degree of insulin resistance at baseline, inflammatory markers’ expression, sample size, study design, technical assays, the timing of assessment of postoperative outcomes, and inherited factors of the study population, which could impact the heterogeneity among the studies.…”
Section: Discussionsupporting
confidence: 92%
“… 3 , 16 Briefly, 100µL blood was incubated with 10µL PerCP-conjugated anti-human CD45 monoclonal antibody (Becton Dickinson Biosciences), 10µL PerCP-conjugated anti-human CD4 monoclonal antibody APC (Becton Dickinson Biosciences, USA), and 10µL allophycocyanin-conjugated anti-human CD27 APC (Becton Dickinson Biosciences, CA, USA) for 30 min at 4°C. 3 , 16 , 17 Briefly, 100µL blood was incubated with 10µL PerCP-conjugated anti-human CD45 monoclonal antibody (Becton Dickinson Biosciences), 10µL PerCP-conjugated anti-human CD4 monoclonal antibody APC (Becton Dickinson Biosciences, USA), and 10µL allophycocyanin-conjugated anti-human CD27 APC (Becton Dickinson Biosciences, CA, USA) for 30 min at 4°C. The number of peripheral blood cells, which was positive for CD markers, was decided by a three-dimensional fluorescence dot-plot analysis of the samples, following the proper gating.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two studies found that some TLR4 polymorphism is linked to a higher probability of developing obesity and metabolic disorders, and this is proof that supports the key role of TLR4 in these diseases [ 217 , 218 ]. Sharif et al [ 219 ] found that the TLR4 D299G/T399I haplotype polymorphism elevates the risk of insulin resistance by elevating TLR4 protein expression in obese subjects.…”
Section: Microbiome Dysbiosis At the Intersection Of Obesity And Glau...mentioning
confidence: 99%
“…Obesity is a kind of chronic low-grade inflammation [11]; hypothalamic inflammation is an important step in the initiation of insulin resistance caused by obesity, and inflammation is associated with many epigenetic changes, thus causing alterations in immune cell function that play an important role in the formation of obesity [12], with special emphasis on the role of the TLR4 signaling pathway [13]. Among them, TLR4 rs4986790 gene polymorphism has been linked with systolic blood pressure level [14,15], insulin resistance, and protein expression in obese patients [16].…”
Section: Introductionmentioning
confidence: 99%